2024
DOI: 10.1136/bmjopen-2022-071504
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of antibiotics self-medication among indigenous people of Bangladesh: a cross-sectional study

Adnan Mannan,
Kallyan Chakma,
Gourab Dewan
et al.

Abstract: ObjectivesSelf-medication with antibiotics (SMA) contributes significantly to the emergence of antimicrobial resistance (AMR), especially in low-income countries including Bangladesh. This study aimed to generate evidence on the self-reported prevalence of antibiotic self-medication and its determinants among indigenous people residing in Bangladesh’s Chittagong Hill Tracts (CHT) districts.DesignThis study used a cross-sectional design with data collected through a survey using a semi-structured questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…In the present study, 76% of cases reported self-medicating with antibiotics for symptoms that most frequently included cough, fever, and sore throat among our participants. Our results are similar to those of several previous studies in the literature [14][15][16]. The Jordanian study by Al-Tarawneh et al showed that all cases of antibiotic use by self-medication were to treat viral infections not requiring antibiotic treatment [17].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 76% of cases reported self-medicating with antibiotics for symptoms that most frequently included cough, fever, and sore throat among our participants. Our results are similar to those of several previous studies in the literature [14][15][16]. The Jordanian study by Al-Tarawneh et al showed that all cases of antibiotic use by self-medication were to treat viral infections not requiring antibiotic treatment [17].…”
Section: Discussionsupporting
confidence: 91%